Implementasi Permendagri Nomor 20 Tahun 2018 Terhadap Pengelolaan Keuangan Desa Di Desa Kampung Baru Kota Pariaman - Munawarti, Munawarti; EDT, Risa Wahyuni; Multama, Ilham (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2022)
The aim of this research is to describe how village finances are managed according to Minister of Home Affairs Regulation number 20 of 2018, starting from the Planning, Implementation, Administration, Reporting and Accountability stages. This research was conducted in Kampung Baru Padusunan Village, East Pariaman District, Pariaman City. This research uses a qualitative descriptive approach with data analysis methods, namely: 1). Reducing data, 2). Data presentation, 3). Draw conclusions/verify. The informants in this research were representatives from the village. The results of the research show that Village Financial Management in Kampung Baru Padusunan Village, East Pariaman District, Pariaman City is generally in accordance with the provisions of Minister of Home Affairs Regulation number 20 of 2018, however there are still several provisions that are still not fully complied with by the Kampung Baru Padusunan Village government, p. This occurs due to delays in financial accountability in management.